Coopetição em clusters comerciais : análise no município de Lagarto – Sergipe - Santos, Obderan Bispo dos (2019)
Cooperation between companies is as irreversible a strategy as globalization, it is understood that relations between cooperating organizations, while competing, provide advantages that can positively influence their results, promoting a competitive chain gain. In this scenario, the phenomenon of coopetition has been highlighted, since it contemplates the analysis of behaviors of competitive cooperation between organizations, that is, competitors that cooperate to generate collective value while competing for individual benefits. In this context, the research analyzes the phenomenon applied to commercial organizations, whose main objective was to analyze the correlation of cooperation and competition with the coopetition among merchants associated with the Chamber of Shopkeepers (CDL) in the municipality of Lagarto/SE. With an exploratory and descriptive character with a quantitative nature, based on the coopetition analysis model developed by Silva (2016), the research development allowed the study of coopetition to be deepened in agglomerated commercial organizations, contributing to the literary development on the theme and, bringing as a suggestion, the inclusion of variables related to culture and trust as influencers in coopetition. For the main results found, the analyzes pointed out the existence of a retail commercial cluster in Lagarto/SE, in addition, it was verified that the women are more cooperative than the men. Finally, the hypotheses of the research were not statistically confirmed, making it unfeasible to assure that there is correlation of cooperation and competition with the coopetition in the researched environment.